2021
DOI: 10.48550/arxiv.2105.06504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutron Star Quantum Death by Small Black Holes

Pierce Giffin,
John Lloyd,
Samuel D. McDermott
et al.

Abstract: Neutron stars can be destroyed by black holes at their center accreting material and eventually swallowing the entire star. Here we note that the accretion model adopted in the literature, based on Bondi accretion or variations thereof, is inadequate for small black holes -black holes whose Schwarzschild radius is comparable to, or smaller than, the neutron's de Broglie wavelength. In this case, quantum mechanical aspects of the accretion process cannot be neglected, and give rise to a completely different acc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…As mentioned, an isolated PBH is commonly assumed, but as PBHs form just after inflation they will interact with the radiation dominated, almost homogeneous early universe. [110] found that accounting for those interactions pushed the minimum mass of PBHs to 10 14 g instead, with [111] reaching a similar conclusion via a very different method of constantly accreting matter instead.…”
Section: Black Hole Evaporationmentioning
confidence: 95%
“…As mentioned, an isolated PBH is commonly assumed, but as PBHs form just after inflation they will interact with the radiation dominated, almost homogeneous early universe. [110] found that accounting for those interactions pushed the minimum mass of PBHs to 10 14 g instead, with [111] reaching a similar conclusion via a very different method of constantly accreting matter instead.…”
Section: Black Hole Evaporationmentioning
confidence: 95%
“…Once again, tidal deformability measurement can in principle be used to break the degeneracy. Additionally, solar-mass BHs can form out of NS transmutation in certain particle-dark-matter scenarios [90][91][92][93]. In the upper half of this mass range (2 ≲ m i =M ⊙ ≲ 3), the component BHs in the binary may form out of previous NS-NS mergers and then pair again to produce a light binary [94].…”
Section: B Pbh Masses and Spinsmentioning
confidence: 99%
“…Arguably, the most natural explanation for such a remarkable claim would be a population of subsolar PBHs which, given current microlensing constraints in that mass range [79], could account for as much as a few percent of the dark matter [12]. In certain particledark-matter scenarios solar-mass BHs can form out of neutron star transmutation [80,81], but lighter BHs can essentially be of primordial origin only (see, however, Ref. [82] for models in which subsolar BHs are born out of dark sector interactions).…”
Section: -3mentioning
confidence: 99%